Proposal for the analysis of changes neo-institutional distribution system in retail food in Venezuela. (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The aim of this study is to formulate a proposal to analyze, from the neo-institutional theory, the changes that have occurred in the retail distribution system of food in Venezuela in recent decades, taking into account the approach of North (1990), who stresses the importance of analyzing the institutional changes to understand the changes that historically occur in economies. For the purpose of achieving the objective, the work was adjusted to the following scheme. In a first part performs a brief description of the major changes that have taken place in the national food distribution, leading to the need for a holistic analysis of those changes. It is held in that part, which part of the neoinstitutional theory could be very useful to start from the premise that those amendments could be explained as a set of institutional changes. Subsequently, we review the theory of neo-institutional, highlighting the fact that agents-saving activity is a determinant of institutional change. We study also the proposal made by Williamson (2000), who suggests to analyze the aforementioned processes of institutional change at four levels: 1) the corresponding variations of informal institutions, 2) associated with changes in the legal framework; 3) the risks associated with changes in the mechanism of vertical coordination of activities, and 4) the reference to the changes in business strategies. In a last part, supports the proposal to analyze the changes that have occurred in the system of food retailing in the country with the use of neo-institutional theory.
Keywords: neo-institutional theory; retail; food distribution; Venezuela